Back Cover: Structural Analysis of Nuclear Spin Clusters via 2D Nanoscale Nuclear Magnetic Resonance Spectroscopy (Adv. Quantum Technol. 3/2020). Issue 3 (6th March 2020) - Yang, Zhiping; Kong, Xi; Li, Zhijie; Yang, Kai; Yu, Pei; Wang, Pengfei; Wang, Ya; Qin, Xi; Rong, Xing; Duan, Chang‐Kui; Shi, Fazhan; Du, Jiangfeng
Abstract : Two‐dimensional nanoscale NMR spectroscopy on a pair of coupled 13C nuclear spins with the nitrogen‐vacancy sensor is demonstrated experimentally by Xi Kong, Fazhan Shi, Jiangfeng Du and co‐workers, article number 1900136 . The structure of the nuclear spin pair is resolved and a step‐by‐step route to characterize a single molecule structure is proposed for the further applications. The picture shows the coupled 13C nuclear spins (blue spots) detected by a nitrogen‐vacancy sensor (the shining spot) in diamond.